THE ROLE OF PLAY IN THE DEVELOPMENT OF PRESCHOOL CHILDS SPEECH - Matmusayeva Muhayo Azamovna (American Journals, 2023)
The article is devoted to the issue of speech development of preschool children through the use of speech games. The idea is substantiated that the initial principle of teaching children to read and write is a "pre-letter", purely sound learning period. Special attention is paid to the systematization of speech development games and the preparation of children for literacy, for the successful further formation of reading and writing skills.
Keywords: Training, active, attention, sound reproduction, correction, optimization, perfection, development, anthropometry, science, speech development, speech characteristics, speech games, kindergarten, preschoolers.